verify that-(-x) is equal to X upon x is equal to 9 upon 13
Answers
Answered by
1
Answer:
Step-by-step explanation:
-(-x) = +x = x
-(-9)/13= 9/13
Hence verified that -(-x)=x; -(-9)/13=9/13
Answered by
0
Answer:
-(-x) = +x
-(-9/13) = 9/13
negative number and negative number is always a positive number
9/13 = 9/13
the answer is true
Hence it is verified
Step-by-step explanation:
Hope it is hopeful
pls mark as BRAINLIEST
Give me thanks and rate the best
Similar questions
Environmental Sciences,
2 months ago
Social Sciences,
2 months ago
Math,
4 months ago
Geography,
4 months ago
Math,
11 months ago
Hindi,
11 months ago